Synergistic Effects of the Lactobacillus acidophilus Surface Layer and Nisin on Bacterial Growth - Prado-Acosta, Mariano (American Society for Microbiology (ASM), 2010)
We have previously described a murein hydrolase activity for the surface layer (S-layer) of Lactobacillus acidophilus ATCC 4356. Here we show that, in combination with nisin, this S-layer acts synergistically to inhibit the growth of pathogenic Gram-negative Salmonella enterica and potential pathogenic Gram-positive bacteria, Staphylococcus aureus and Bacillus cereus. In addition, bacteriolytic effects were observed for the Gram-positive species tested. We postulate that the S-layer enhances the access of nisin into the cell membrane by enabling it to cross the cell wall, while nisin provides the sudden ion-nonspecific dissipation of the proton motive force required to enhance the S-layer murein hydrolase activity.